Kua rangitamiro mai nei : we have assembled here : Masters of Māori Visual Art, Te Kunenga ki Pūrehuroa Massey University - Konia, Brook Frederick Charles (Massey University, 2023)
“Wehea te muka, kua whati te taura, whiria kia mau, kia ū he taura mau waka.” Ko te aukaha hei here i ngā waka, te pūtake o tēnei mahi toi. Tēnei aukaha e here ana i ngā rākau ki te taura me te puru. I konei ka miro i te muka tī kōuka hei taura whiri. Kua purua te kōhao ki te puru rākau, he puru tāwhao, he puru mānuka. Ko ngā tārai he rākau e whai pānga ana ki taku ngākau, he paketai, he kōporo, he paraki mira anō hoki, hei tohu i te mana whakapapa, i te whanaungatanga, me te manaakitanga. Ko tā te paepae tāutuutu, he hiki i te tapu, he tuitui i te tāngata kia piri, kia kotahi. “Wehea te muka, kua whati te taura, whiria kia mau, kia ū he taura mau waka.” "Separated fibres may break, yet when bound tightly together, they can meet any challenge." 'Kua Rangitāmiro Mai Nei' delves into the wood-joinery technique of aukaha (lashing) used in waka construction. I have explored aukaha through the tī kōuka (cabbage tree/cordyline australis), collecting and processing the rau (leaves) to create taura (ropes), revealing the function and design. Exploring aukaha and lashing together, found and collected rākau that carry personal connection of whakapapa, whakawhanaungatanga and manaakitanga - creating puru plugs and block-shaped components from these rākau. 'Kua Rangitāmiro Mai Nei' shares mātauranga of the strength in assembling and working together. In the metaphoric language of whaikōrero and mihimihi emboldened at the paepae, kupu whakarite is masterfully spoken, words used that allegorically reflect inherent qualities seen in nature that appropriately share the roles and responsibilities tāngata have to a place. In presenting two seats facing each other to conceptualise the paepae and words spoken there, this body of work considers the potential of joining and working together.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)